Rare occurrence of Nautilus sp. fossils from Batangas, Philippines - Castro, Abigael L.; Marquez, Dorothy Joyce D.; Nogot, Jaan Ruy Conrad P.; Javellana, Geleen Rica S. (2020)
Two nautilid (Cephalopoda, Mollusca) fossils are discovered from an exposure of the late Miocene ? early Pliocene Calatagan Formation in Talim Point, Lian, Batangas, southwestern Luzon. They were identified as Nautilus sp. because of the similarity in conch shape and sutures to those of extant species of Nautilus. The two Nautilus specimens were found in a fine- to medium-grained sandstone unit and observed to be associated with other macrofossils such as corals, gastropods, bivalves, brachiopods, and echinoids. The age of the Nautilus specimens was determined through the analysis of the planktonic foraminifera in the sandstone matrix. These specimens represent the oldest fossil record of Nautilus in the Philippines. (Author's abstract)